Computational studies of the size-effect and temperature on the electronic structure and stability of TiO2 nanoclusters - Sánchez Naranjo, Jennifer Anaís (2021)
Titanium oxide with three different crystalline phases is an important transition metal oxide due to its photocatalytic, electronic, and even biological properties. However, the performance of the TiO2 nanoclusters strongly depends on their size, shape, organization. Even though theoretical studies of TiO2 nanoclusters have been largely performed, some challenges are still needed to solve in order to utilize its properties in the most practical way. A combination of semi-empirical density-functional tight-binding (DFTB) with ab initio density-functional theory (DFT) methods will allow us to predict and study TiO2 nanoclusters, such that we can resolve the most stable nanocluster topology given two constrains: the number of TiO2 molecules and the temperature T. Molecular dynamics simulations are applied to resolve the most likely atomic structure of n(TiO2) (n = 1–10) nanoclusters at a room temperature. The electronic structure of the most likely candidates are computed using ab-initio DFT at the level of hybrid functional B3LYP. Physical-chemical properties like electronic energy, nuclear repulsion, dipole moment, quadrupole moment, polarizability, HOMO, LUMO, band gap, zero-point energy and gyration radius are also predicted.